Radiolarian-based sub-surface temperatures over the last 40 kyrs in core MD12-3396CQ northeast of Kerguelen Island, Southern Ocean - Matthieu Civel-Mazens; Xavier Crosta; Giuseppe Cortese (PANGAEA, 2021)
Radiolarian census counts were used to quantitatively estimate summer sub-surface temperatures (sub-ST) over the last 40,000 years in core MD12-3396CQ, collected in 2012 on board the R.V. Marion Dufresne northeast of Kerguelen Island, Southern Ocean. The transfer function used to reconstruct summer (Janunary to March) Sub-ST (200 meters deep) is the Imbrie and Kipp method that here uses 207 surface sediment samples, the relative abundances of 81 radiolarian taxa and 5 factors (Civel et al., 2021). This method yields a root mean square error of prediction of ~1.5 °C. The core chronology is detailed in Gottschalk et al. (2020).